Nursing approach to tobacco users in primary health care - Vanderleia Soéli de Barros Zampier; Marcelo Henrique da Silva; Renata Evangelista Tavares Machado; Rodolfo Ribeiro de Jesus; Maria Cristina Pinto de Jesus; Miriam Aparecida Barbosa Merighi
ABSTRACT Objective: to understand the experience of nurses in the approach to tobacco users in primary health care services. Method: Qualitative, phenomenological research with 15 nurses who were interviewed between January and March 2017. Their speeches were analyzed and classified into categories. Results: the approach by nurses to tobacco users is performed in an individual and unsystematic manner and in operative groups in accordance with the principles of the cognitive-behavioral therapy. This is a complex approach due to issues related to users themselves and to human, material, and structural resources. The expectations of nurses include supporting smoking cessation and expanding the tobacco use prevention work in educational environments. Final considerations: this study points out that nurses need to use the nursing care systematization in coordination with the recommendations of policies aimed at tobacco use control to perform their role in the promotion, control, and reduction of health complications in tobacco users.